The travel writings of Marguerite Blessington : the most gorgeous lady on the tour - Lipska, Aneta (Anthem studies in travel, 2017)
"This book derives from the conviction that Marguerite Blessington (1788-1849) merits scholarly attention as a travel writer, and thus offers the first detailed analysis of Blessington's four travel books: 'A Tour in The Isle of Wight, in the Autumn of 1820' (1822), 'Journal of a Tour through the Netherlands to Paris in 1821' (1822), 'The Idler in Italy' (1839) and 'The Idler in France' (1841). It argues that travelling and travel writing provided Blessington with endless opportunities to reshape her public personae, demonstrating that her predilection for self-fashioning was related to the various tendencies in tourism and literature as well as the changing aesthetic and social trends in the first half of the nineteenth century."--